Painéis não estacionários e previsibilidade ao nível da empresa na presença de quebras estruturais e dependência nas seções transversais - Rivera, Edward Bernard Bastiaan de Rivera Y (2014)
The contribution of this thesis is the application of a new perspective in the assessment of the rational expectations model at the enterprise level, conducted in Nasseh and Straus (2004), Goddard, McMillan and Wilson (2008) and Rivera Rivera, Martin, Marçal and Basso (2012). These works investigate micro efficiency hypothesis in the sense presented in Jung and Shiller (2005) and adopt the restrictive hypotheses of independence in the error terms of the sample companies, as well as the absence of structural breaks. Common movements in stock prices characterize the systematic risk from unobserved common factors and structural breaks, such as financial crises, induce shifts in the relationship between prices and fundamentals. The objective of this investigation is the analysis of the rational expectations model at the enterprise level with constant and time-varying returns under the presence of multiple structural breaks and cross-sectional dependence. Recent econometric procedures of panel unit root and cointegration that contain properties of structural breaks and dependences are applied to Sao Paulo Stock Exchange (Bovespa) and S&P100 companies quarterly data covering the period of 1994-2012. Considering a multifactor error structure, results indicate a failure in the rejection of a unit root in (log) prices and (log) dividends. Panel cointegration analysis allowing structural breaks and cross-sectional dependence controlling to the presence of bubbles indicate that established procedures might not detect present structural breaks or generate oscilating statistics in size and power depending on the panel dimensions. A computational extention is developed allowing for enterprise-level structural breaks and cross-sectional dependence through bootstrap techniques. Results fail to reject the rational expectations model at the enterprise level and are consistent with the statistical significance and break dates detected in time-series cointegration routines. Evidences favor rationality and unforecastability of returns, where investors cannot profit consistently through speculation and active portfolio management.